2019
DOI: 10.3389/fmed.2019.00287
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Performance on a Virtual Reality Cognitive Stimulation for Use in the Intensive Care Unit: A Non-randomized Trial in Critically Ill Patients

Abstract: Background: Newly acquired long-term cognitive impairments are common among survivors of critical illness. They have been linked to the stressful situation that patients experience in the intensive care unit (ICU). In this paper we use virtual reality (VR) technology to comfort critically ill patients and reduce stress during their ICU stay. We investigate the acceptance, comfort, recollection, and visual perception of VR stimulation and how it affects physiological parameters. Methods: A VR head-mounted displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 38 publications
(38 reference statements)
3
36
1
Order By: Relevance
“…In line with previous findings on VR modalities in the intensive care, our results show that this newly designed ICU-VR module is safe ( 31 33 ). As noted previously, a VR meditative intervention can be implemented during an ICU stay ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous findings on VR modalities in the intensive care, our results show that this newly designed ICU-VR module is safe ( 31 33 ). As noted previously, a VR meditative intervention can be implemented during an ICU stay ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…This 29-item self-report tool measures volunteers’ involvement in many different daily activities such as watching television, reading books, or enjoying movies. Those who have the ability to become more involved or engrossed in these activities will also have greater immersive tendencies and will more easily feel present in virtual environments ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the ratings of acceptance and usability were very high and close to the maximum score. Gerber et al (2019a) found similar values, using a comparable technical setup with critically ill patients in the intensive care unit (ICU). Secondly, the ratings in the SSQ showed very low values, thus reflecting a safe device regarding cybersickness.…”
Section: Acceptance Usability and Side Effectsmentioning
confidence: 63%
“…After having finished the task, all participants were asked to fill out a questionnaire on usability, negative effects, and general demographic data. The questionnaire was slightly adapted, for our study, from Gerber et al (2019a). The content regarding usability was based on the System Usability Scale (SUS; Brooke, 1996), the content regarding side effects on the Simulator Sickness Questionnaire (SSQ; Kennedy et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…These systems can be used to avoid bad habits, addictions or aggressive behavioral responses [ 30 , 31 , 32 ]. Cognitive stimulation is a fundamental strategy for the improvement and rehabilitation of mental capacities and executive functions, such as memory, attention, processing speed, and contextual learning [ 33 , 34 ], evaluating in this way the behavior of the participants and improving the conditions that unbalance their state of mental well-being [ 35 ]. Although the literature does not allow establishing the full effectiveness of IVR to counteract disorders such as dementia, potential distractors are reduced and the experience of people with mild cognitive impairment is improved [ 36 ].…”
Section: Introductionmentioning
confidence: 99%